2019
DOI: 10.1253/circj.cj-19-0410
|View full text |Cite
|
Sign up to set email alerts
|

Insights From 10-Year Outcomes of Mesenchymal Stem Cell Transplantation in Heart Failure Patients

Abstract: cardiac function in rodents. 2 Since the mid-2000 s, clinical trials, including randomized controlled trials (RCTs), using bone marrow-derived MSCs (BMMSCs) have been conducted. 3 A meta-analysis of cell therapy studies using bone marrow-derived cells, including BMMSCs (50 studies, 2,625 recipients) demonstrated that patients receiving cell therapy resulted in improvement of LV function with greater EF (+3.96%), reduced infarct size, and smaller LV volume. 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that stem cell transplantation has a certain therapeutic effect on CF [ 14 ], but MSCs after transplantation have deficiencies such as low survival rate and low homing size, and their safety is still unclear. Potential immune response and tumorogen risk limit the direct application of MSCs [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that stem cell transplantation has a certain therapeutic effect on CF [ 14 ], but MSCs after transplantation have deficiencies such as low survival rate and low homing size, and their safety is still unclear. Potential immune response and tumorogen risk limit the direct application of MSCs [ 15 ].…”
Section: Introductionmentioning
confidence: 99%